PENERAPAN METODE THE SIGNAGE PYRAMID (TSP) MODEL PADA ANGKOT STOP SIGNAGE DI KOTA BANDUNG - Aria Ar Razi; Intan Suci Lestari (Universitas Negeri makassar, 2021)
Stop signs for public transportation as visual communication placed on pedestrian areas serve to provide information as a sign where public transportation must stop and become a place where passengers can wait for a ride. In 2016 the City of Bandung through the Department of Transportation imposed a stop sign with a new design. This change was made in connection with the Bandung Urban Mobility Project (BUMP) as one of Bandung's visions to become a smart city. The purpose of the sign is to meet the needs of the community in carrying out activities using public transportation to stop at the right place. But in reality, there are still many people who misunderstand the function of signs because they are considered unable to meet their needs. The purpose of this study was to evaluate signage based on user experience, especially on Angkot stop signs designed by Kudos Design Collaboratory. By using The Signage Pyramid Model (TSP) method for analysis, this study will provide evaluation results and recommendations for the Angkot Stop Signage design concept that has taken into account the needs and experiences of public transport users.Keywords: User Experience; Signage; Stop Signage; TSP; Environmental Graphic Design